Pendampingan Lembaga PAUD di Desa Bugis Kabupaten Bima Saat Masa Pandemi: Kegiatan Belajar Mengajar dan Sosialisasi Covid-19 - Qadafi, Muammar; Agustiningsih, Neneng; Nuralisa; Nurwahidah, Ida; Febiyanti, Meysa (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
The emergence of the Covid-19 pandemic has had a very significant impact on people's lives, including the implementation of early childhood education. This service was initiated because of the condition of the people who were very confused with a learning system that was very different from the normal conditions that had been carried out so far, so there was a need for assistance, both for teachers at school and for parents who were at home because the learning system used the learning system from house. The method used consists of several stages, namely: initial survey/observation, visiting residents' homes to socialize activities, implementing community service, consultation and learning at school and at home, and evaluation. The results of the service show that teachers in early childhood institutions are greatly assisted by the presence of students who carry out community service by assisting in the implementation of learning, socialization of healthy living during a pandemic, and assistance to parents to ensure that the implementation of learning at home runs smoothly as expected by the teacher.